Penerapan Model Pembelajaran Discovery Learning Berbantuan GeoGebra Pada Materi Fungsi Kuadrat Untuk Meningkatkan Hasil Belajar Siswa Fase E Perhotelan 4 SMK Negeri 1 Sukasada Semester Ganjil Tahun Pelajaran 2022/2023 - Made Pradnyana (STAHN Mpu Kuturan Singaraja, 2023)
Based on the results of the research and discussion, it can be concluded that the use of Geogebra learning media in the application of discovery learning can improve the mathematics learning outcomes of Phase E students in Hospitality 4 odd semesters for the 2022/2023 academic year, with an average classical cycle I of 70.93 with an absorption power of 70.93%. and classical learning completeness of 72.72% to an average classical learning result of.75.84 with an absorption power of 75.84% and classical completeness of 87.87% in cycle II